Profiles of Problematic Internet Use in Bullying and Cyberbullying among Adolescents - Méndez, Inmaculada (Int J Environ Res Public Health, 2020)
The rise of technology has increased risks such as problematic internet use or cyberbullying. Data show that there is problematic use of the internet, which has important repercussions academically, personally, socially and for health. The objective of this study was to identify different profiles that vary according to intra- and interpersonal conflicts related to internet use. In addition, this study aimed to examine whether there are significant differences in bullying and cyberbullying among adolescents with a conflict related to internet use. The study participants were 810 students of Compulsory Secondary Education (M = 13.99, SD = 1.32). The Questionnaire on School Violence and the Questionnaire of Experiences Related to Internet was use. The latent profile analysis identified four different types of conflicts related to internet use: (a) high levels in intra- and interpersonal conflicts; (b) low levels intra- and interpersonal conflicts; (c) moderate intra- and interpersonal conflicts and (d) very high levels in intra- and interpersonal conflicts. The results of the study indicated that there were significant differences in the manifestations of school violence between the profiles. This study assists in educational programs to prevent conflicts related to internet use and school violence through emotional adjustment.